2015
DOI: 10.1128/aac.01146-15
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of [ 11 C]Rifampin Pharmacokinetics within Mycobacterium tuberculosis-Infected Mice by Using Dynamic Positron Emission Tomography Bioimaging

Abstract: e Information about intralesional pharmacokinetics (PK) and spatial distribution of tuberculosis (TB) drugs is limited and has not been used to optimize dosing recommendations for new or existing drugs. While new techniques can detect drugs and their metabolites within TB granulomas, they are invasive, rely on accurate resection of tissues, and do not capture dynamic drug distribution in the tissues of interest. In this study, we assessed the in situ distribution of 11 C-labeled rifampin in live, Mycobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…The presence of multiple different pulmonary lesions in C3HeB/FeJ mice was described recently ( Irwin et al, 2015 ), but cavitation was a rare event under the conditions evaluated. Because several TB drugs with differing physicochemical properties have been shown to partition differently into these lesions in a manner similar to observations in humans and/or rabbits ( DeMarco et al, 2015 ; Irwin et al, 2016 ; Kjellsson et al, 2012 ; Lanoix et al, 2016b ; Prideaux et al, 2015 ; Weinstein et al, 2012 ), and because the activity of some drugs might be modulated by conditions within large caseous lesions ( Lanoix et al, 2015 , 2016a ), the more tractable and economical C3HeB/FeJ mouse model that exhibits these multiple lesion types provides an important new tool for TB drug development research.…”
Section: Discussionmentioning
confidence: 63%
“…The presence of multiple different pulmonary lesions in C3HeB/FeJ mice was described recently ( Irwin et al, 2015 ), but cavitation was a rare event under the conditions evaluated. Because several TB drugs with differing physicochemical properties have been shown to partition differently into these lesions in a manner similar to observations in humans and/or rabbits ( DeMarco et al, 2015 ; Irwin et al, 2016 ; Kjellsson et al, 2012 ; Lanoix et al, 2016b ; Prideaux et al, 2015 ; Weinstein et al, 2012 ), and because the activity of some drugs might be modulated by conditions within large caseous lesions ( Lanoix et al, 2015 , 2016a ), the more tractable and economical C3HeB/FeJ mouse model that exhibits these multiple lesion types provides an important new tool for TB drug development research.…”
Section: Discussionmentioning
confidence: 63%
“…Dynamic PET can provide multi-compartment analyses at multiple time points, allowing the characterization of radiolabeled drug concentrations in multiple tissues simultaneously. Previous studies with whole-body PET bioimaging in murine models of TB have provided valuable information about the pharmacokinetics of the first-line TB drugs isoniazid (2-[ 18 F]fluoroisonicotinic acid hydrazide, [ 26 ]) and rifampin ( 11 C-rifampin, [ 27 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting group of infection-selective radiotracers is the labeled siderophores, which have shown promising results for the imaging of infection caused by Aspergillus fumigatus [ 41 ]. Previous studies on imaging of Mycobacterium tuberculosis infections have also identified potential radiopharmaceuticals that may replace 18 F-FDG in the future [ 42 , 43 ]. Nevertheless, investigations on infection- and inflammation-selective radiopharmaceuticals are still in their infancy, and novel approaches need to be evaluated in different model systems.…”
Section: Discussionmentioning
confidence: 99%